The pattern of gestational weight gains among Chinese women: a repeated measure analysis. Issue 1 (December 2018) - Tan, Jing; Ren, Yan; Qi, Yana; Chen, Peng; Tang, Li; He, Guolin; Li, Sheyu; Sun, Xin; Liu, Xinghui
Abstract This study aimed to investigate the pattern of gestational weight gain (GWG) among Chinese women. We included pregnant women, who delivered at a referral medical center in China and had no pre-specified adverse pregnancy outcomes. We collected weight data across all pregnancy visits, and used the two-level spline linear model to fit for the pattern of GWG according to pre-pregnancy BMI categories. In total, 4, 567 pregnant women with 47, 699 repeated measures were eligible. For those who were underweight, normal and overweight before pregnancy, the interquartile ranges (25th to 75th quartiles) of GWG between 14 and 36 gestational weeks were 12.9–17.7 kg, 12.6–17.3 kg and 11.7–16.8 kg, and the corresponding rates of GWG were 2.62 kg/month, 2.56 kg/month and 2.37 kg/month. For underweight and normal women, the rates of GWG were similar before 14 weeks (0.57 and 0.58 kg/month) and after 36 weeks (1.69 and 1.70 kg/month); however, the rates of GWG were higher for overweight women (0.66 kg/month before 14 weeks and 1.89 kg/month after 36 weeks). In summary, the pattern of GWG among Chinese pregnant women is generally consistent with the IOM recommendation, particularly for those who are normal or underweight. Modifications are, however, warranted for overweight pregnant women.